Conservation behavior and effects of economic and environmental message frames. Issue 6 (26th August 2020) - Reddy, Sheila M.W.; Wardropper, Chloe; Weigel, Collin; Masuda, Yuta J.; Harden, Seth; Ranjan, Pranay; Getson, Jackie M.; Esman, Laura A.; Ferraro, Paul; Prokopy, Linda
Abstract: Emphasizing the economic and environmental benefits of conservation is business‐as‐usual for environmental organizations seeking to influence conservation behavior, but these message frames are rarely tested. We embedded a large message framing experiment into the recruitment for a conservation agriculture program targeting farmland owners in the Mississippi River Basin. We found that framed messages do not increase enrollment in the agricultural program—the desired conservation behavior—compared to an informational message (control) and may decrease enrollment among farmland owners not already using conservation practices (i.e., cover crops).